Capital Tax Competition and Partial Cooperation : Welfare Enhancing or not? - Holger Kächelein (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2004)
The paper analyzes under which conditions a partial tax cooperation will be welfare enhancing within the cooperating regions. Starting from the standard symmetric tax competition model, subgroups of regions can form tax cooperations and thereby increase their relevant market share. As the noncooperation regions react to the tax change in the bloc, the welfare outcome relative to the symmetric case is ambiguous. Complementary to a more general theoretical approach, a simulation is also used to clarify the limits of welfare enhancing partial tax coordination of a subgroup of regions. In the used structure, only if regions are very large, tax rates are complements. However, the case of welfare loss due to a partial tax harmonization is mainly limited to the case of a single cooperation.
Keywords: H25; F21; H26; 330; Capital Tax Competition; Tax Harmonization; Asymmetric Tax Competition; Kapitalertragsteuer; Steuerwettbewerb; Steuerharmonisierung; Landesgrösse; Wohlfahrtseffekt; Theorie